Comparison of Wound Infection with Absorbable Suture Versus Non-Absorbable Suture after Cesarean Section - Maria Siddiqui, Syeda Sahar Zahra, Syeda Taskeen Ejaz, Bazgha Sahar, Nabila Eajaz, Saima Raees Ahmad (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the frequency of wound infection with absorbable suture and non-absorbable suture after cesarean section. Study Design: A randomized controlled trial. Place and Duration: Department of Obstetrics and Gynaecology, Nisthar Hospital, Multan from August 2021 to June 2022. Methodology: A total of 826 women (413 in each group) undergoing cesarean section were included. In Group-A absorbable suture was employed while in Group-B, non-absorbable suture was used. Post-operatively, all patients were followed up weekly and the final assessment of wound infection was done after 15 days. Results: In a total of 826 cases, mean age was 26.47±3.42 years. Mean body mass index was 25.62±1.87 kg/m2 and obesity was present in 166 (20.1%). Of these 826 study cases, emergency cesarean section was performed in 593 (71.8%). Mean duration of procedure was 38.43±12.21 minutes and 562 (68.0%) had duration of procedure below 40 minutes. Overall, wound infection was noted in 145 (17.6%) women, In Group-A, wound infection was noted in 96 (23.2%) women and in Group-B it was in 49 (11.9%) (p<0.0001). Practical Implications: Clinicians can employ non-absorbable sutures to decrease the risk of post-operative wound infection after cesarean section. Conclusion: We found non-absorbable sutures after cesarean section to yield significantly less rates of wound infection when compared to absorbable sutures. Keywords: Absorbable suture, Non-absorbable suture, wound infection, cesarean section.